PRE-SERVICE TEACHERS' PERCEPTIONS OF THE USE OF GENAI AND TRADITIONAL GRAMMAR-CHECKING TOOLS FOR ENGLISH WRITING - Tiara Putri; Rahmah Fithriani (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
The increasing utilization of artificial intelligence in English language learning and teaching emphasizes the necessity of understanding pre-service teachers’ perceptions on AI-writing tools. This study investigates their perspectives on the use of Generative AI (GenAI) tools such as ChatGPT and GeminiAI and traditional grammar checkers such as Grammarly and Quillbot in English writing. Employing a qualitative case study approach, data were collected from 15 pre-service English teachers through questionnaires and in-depth interviews with five selected participants. Findings reveal that GenAI tools are perceived as beneficial for idea development and providing comprehensive feedback, whereas traditional grammar checkers are valued for their grammatical accuracy and structural refinement. Accessibility is a determining factor, with GenAI favored for its unrestricted free features, while grammar checkers often necessitate paid versions for full functionality. However, challenges arise concerning the complexity of AI-generated feedback and the potential for over-reliance, which may hinder independent writing development. Ethical concerns, particularly regarding data privacy and originality, are also identified. From a pedagogical perspective, while these tools support language learning, excessive dependence may undermine critical thinking and writing autonomy. Therefore, teacher education programs should incorporate structured training on the responsible integration of AI and grammar checkers to ensure that pre-service teachers develop both technological proficiency and pedagogical strategies for fostering students’ independent writing skills.